Komunikasi Penutur Bahasa Arab Na>Tiq dan Ghairu Na>Tiq dalam Membangun Komunikasi yang Efektif : (Studi Kasus Pelajar Indonesia dan Na>Tiq di Timur Tengah Tahun 2024) - Bahrul Jadid; Khomsiyatul Mukarromah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Arabic plays a significant role as an international language, especially in the Middle East, which is a primary destination for Indonesian students seeking education. However, communication between native speakers (natiq) and non-native speakers (ghairu natiq) often faces obstacles due to dialectal differences, cultural disparities, and limited language comprehension. This study aims to analyze the communication patterns between these two groups, identify challenges in communication, and explore strategies used to achieve effective communication. Using a qualitative method with a case study approach, data were collected through in-depth interviews with Indonesian students and native Arabic speakers in the Middle East and analyzed using NVivo software to identify communication patterns and language accommodation strategies. The results indicate that effective communication can be achieved through a balance between linguistic competence and cultural understanding, while the main obstacles include dialectal variations, the use of local idioms, and the speaking speed of native speakers. To overcome these challenges, Indonesian students employ strategies such as linguistic convergence, increased cultural understanding, and adaptation to social contexts and conversational situations. The conclusion of this study emphasizes that cultural awareness and language adjustment are key factors in establishing effective communication between natiq and ghairu natiq, and it is expected to serve as a reference for students, educational institutions, and policymakers in designing more effective cross-cultural communication training programs.